THE POSITIVE EFFECT OF THE AROMA OF MARIGOLD LEAF SLICES ON MOSQUITO REPELLENT - Rustam Aji; Jusuf Kristianto; Riang Adeko; Gustomo Yamistada; Jessy Novita Sari (Jurnal Health Sains, 2023)
Aedes aegypti mosquitoes, can cause fever, mosquitoes develop in the transition season. Countermeasures by eradicating vector life cycles, by killing mosquito larvae, using fogging, abate powder, which have an effect on the environment. Researchers were looking for a safe and effective natural larvicide solution, researchers looked at marigold plants at the study site. Marigold plants contain essential oils effective as larvicides in mosquitoes Culex quinquefasciatus, Anopheles stephensi and Aedes aegypti. Quasi-experimental research, cross sectional study design. The purpose of knowing the positive effect of the aroma of marigold leaf slices on mosquito repellent as a repellent. The indoor research site provided mosquito net boxes.containing 136 mosquitoes. The results of the Chi-square analysis obtained P = 0.04 < α 0.05, statistically there was a significant positive effect between marigold leaf slices on mosquito repellent, with odds ratio = 4.10 times. In order for students to get used to it, put slices of marigold leaves in the room to repel mosquitoes.